Transformasi Pola Keuangan Santri melalui Sistem Cashless di Pondok Pesantren Idrisiyyah Putri Tasikmalaya - Sopiatunisa, Neneng; Budiono, Irfan; Gapur, Ega Abdul (JES (Jurnal Ekonomi Syariah), 2025)
This study aims to examine the impact of implementing a non-cash transaction system using QRIS and the Digitren application at the Pondok Pesantren Idrisiyyah Putri Tasikmalaya on the financial behavior of santri. The focus of the research includes discipline in financial management, transparency of transactions, consumption patterns and spending habits, as well as santri's understanding of financial literacy from their own perspective. This research uses descriptive qualitative methods, with data collected through observation, interviews, and documentation. In-depth interviews were conducted with ten female santri, two pesantren financial staff, and one canteen manager. The sampling technique used purposive sampling. The results showed that the implementation of the cashless system succeeded in improving the efficiency of santri financial management, reducing the risk of losing cash, and limiting excessive consumption outside the pesantren environment. Despite facing challenges such as top-up queues and limited direct balance access for santri, the pesantren has implemented adaptive strategies, including extending top-up service hours and providing free cash exchange services. Significantly, this system has changed the pattern of managing santri pocket money to be more structured, helped control their consumptive behavior, and instilled the values of honesty and discipline in financial matters.